Co-authorship network of national researchers of Social Sciences in Mexico //Red de coautoría de investigadores nacionales en Ciencias Sociales en México - Lámbarry-Vilchis, Fernando; Moreno-Jiménez, Juan Carlos (Revista de la Universidad del Zulia, 2020)
Abstract In Mexico, the most outstanding researchers are distinguished by the National Council of Science and Technology. Although, in the international literature, researcher’s co-authorship networks and their impact on efficacy have been studied, in Mexico this type of studies is showing a greater boom, so the objective of this paper is to analyze the structure of the network of co-authorships of the researchers in Social Sciences level 3 of the country. For this purpose, the research method was based on the theory of networks and specifically on topology metrics. One of the conclusions of the research is that the researchers under study publish in a similar proportion individually or collaboratively, configuring a fragmented co-authorship network with a main component with properties that are explained by both the small-world and the free-scale model. Resumen En México los investigadores más destacados son distinguidos por el Consejo Nacional de Ciencia y Tecnología. Aunque en la literatura internacional se han estudiado las redes de coautoría de los investigadores y su impacto en la eficacia, en México este tipo de estudios están presentando mayor auge, por lo que el objetivo de este trabajo es analizar la estructura de la red de coautorías de los investigadores en Ciencias Sociales nivel 3 del país. Para ello, el método de investigación se fundamentó en la teoría de redes y específicamente en las métricas de topología. Una de las conclusiones de la investigación es que los investigadores bajo estudio, publican en similar proporción en forma individual o colaborativamente, configurando una red de coautoría fragmentada con un componente principal con propiedades que se explican tanto por el modelo de mundo pequeño, como de libre escala.